The scientific concepts in biology textbooks - Ornelas, M. (2020)
Learning a science requires the understanding of its language, and the textbook as an educational resource, stands out in the whole teaching process, particularly in the years before the national tests. To what extent, do biology textbooks represent a strategic instrument for teaching and learning and a vehicle of the curricular message? All biology concepts covered and defined in the two biology 10th grade textbooks that are most adopted in Portugal, were quantified using a comparative study. The results showed that these textbooks covered more than 90% of the concepts recommended in the curriculum guidelines, although the total number of concepts was 6.5 to 7.5 times bigger than suggested.